Subpolar Activation of Halogen Heterogeneous Chemistry in Austral Spring - Brian Zambri; Douglas E. Kinnison; Susan Solomon (Geophysical Research Letters)
Abstract Heterogeneous halogen chemistry plays a dominant role in driving changes in polar chemical composition and ozone depletion. Activation of halogens outside the polar regions may result in depletion of local ozone, along with changes in the chemical budgets of various species in the lower stratosphere (LS). In this study, the means and distributions of NO2 measurements from the Stratospheric Aerosol and Gas Experiment III (SAGE3m) are compared to simulations from a coupled climate‐chemistry model, in order to better characterize and quantify subpolar heterogeneous halogen chemistry. NO2 abundances from a simulation with heterogeneous chemistry are drawn from the same distribution as the SAGE3m observations, while the NO2 distribution is different in a simulation without heterogeneous chemistry. Results indicate that heterogeneous chemistry plays a significant role in determining the chemical composition of the subpolar LS in austral spring and show how analysis of distribution functions can provide useful insights into chemical processes.